Efeminasi sebagai pendahuluan kepada pembentukan seorang mak nyah (Effeminacy as a Prelude to being a transsexual) - Md. Noon, Hazizan (2011)
The paper first divides the stages of being a transsexual into three namely: the pre-transsexual, the transsexual and post-transsexual periods (the last stage is applicable only to a transsexual who has abandoned his transsexual status). The paper focuses on the first stage i.e. the stage before someone develops into a full-blown transsexual. The discussion was based on the belief that one possible situation that is associated with being transsexual is one’s effeminate behavior prior to becoming a transsexual. An effeminate is a male behaving like a woman. The paper discusses the main factors of effeminacy as perceived by the non-transsexuals from among the normal male population as well as the effeminates’ friends. It than highlights the way the effeminates look at themselves including the factors that led to their effeminate behavior and others. Other aspects discussed include the characteristics of transsexuals, their activities and also their views on various issues. A comparison between the emic and the outsiders’ views is made for establishing the gap between the two. The paper ends with some suggestions which may be considered in addressing the issue of transsexuals including development of module as aimed by the organizer.